2015
DOI: 10.1126/science.aac5017
|View full text |Cite
|
Sign up to set email alerts
|

Dengue viruses cluster antigenically but not as discrete serotypes

Abstract: The four genetically divergent dengue virus (DENV) types are traditionally classified as serotypes. Antigenic and genetic differences among the DENV types influence disease outcome, vaccine-induced protection, epidemic magnitude, and viral evolution. We characterized antigenic diversity in the DENV types by antigenic maps constructed from neutralizing antibody titers obtained from African green monkeys and after human vaccination and natural infections. Genetically, geographically, and temporally, diverse DENV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
208
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(229 citation statements)
references
References 64 publications
11
208
0
2
Order By: Relevance
“…The sequence of infecting serotypes has been shown to be important in other cohorts and settings (29,30). In future studies, by using higher-resolution antigenic and epidemiological data, it may be possible to identify the specific antigenic relationship between the 1°and 2°infecting DENV isolates, particularly if using Nicaraguan strains, rather than prototype isolates, for the neutralization assays (32).…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of infecting serotypes has been shown to be important in other cohorts and settings (29,30). In future studies, by using higher-resolution antigenic and epidemiological data, it may be possible to identify the specific antigenic relationship between the 1°and 2°infecting DENV isolates, particularly if using Nicaraguan strains, rather than prototype isolates, for the neutralization assays (32).…”
Section: Discussionmentioning
confidence: 99%
“…It has been inferred that the linkage between subtypes and serotypes was less strict than what was classically thought. However, it remains statistically very strong (Katzelnick et al, 2015). The four subtypes are stable since at least 1943, and circulate sympatrically, especially in Latin America and Asia, which provides ample opportunity for mating (Messina et al, 2014).…”
Section: Virusesmentioning
confidence: 99%
“…[7] Some residents suffered haemorrhagic manifestations now associated with repeat infections involving another of the four DENV types. [2,[8][9][10][11][12] A 1996 SAMJ editorial suggested that the 1926/27 epidemic occurred during a brace of remarkably wet years when the rainfall was five and eight times greater than the historical average. [13] However, the Durban rainfall during 1925/26 was the lowest then on record and drought persisted through the first months of the 1927 epidemic, before plentiful March rains.…”
Section: Editorialmentioning
confidence: 99%